Asbestos and Mesothelioma - Testa, Joseph R. (Current Cancer Research, 2017)
This volume is comprised of a multidisciplinary assessment of the interplay between asbestos and cancer as well as new research about the biology and treatment of malignant mesothelioma. Chapters on the various types of asbestos and other mineral fibers, epidemiology, history and future of asbestos-related diseases are included. Other reviews present new information about the role of asbestos-related inflammation and genetic factors, including the role of inherited mutations of BAP1, in mesothelioma causation, as well as recent research about gene signatures, cell signaling, and epigenetic mechanisms in asbestos-related diseases. Other chapters provide updates of novel disease biomarkers and prevention, mechanistic lesson from genetically engineered mouse and 3-D models of mesothelioma tumorigenesis and therapeutic resistance. Also included are up-to-date reviews of surgical, molecularly targeted chemotherapeutic, and immunotherapeutic approaches for mesothelioma as well as an overview of legal issues.